Funkcjonowanie nazwisk pochodzenia niemieckiego w siedemnasto- i osiemnastowiecznych rejestrach poznańskich podatników czopowego. Świadectwa polonizacji - Nowak, Ewa (Poznańskie Studia Polonistyczne. Seria Językoznawcza, 2012)
The proposed paper presents the functioning of German-origin names with their root and etymology of German origin borne by Poznań burghers in the seventeenth and the eighteenth centuries. The source material for the study was provided by archival registers of the taxpayer of the tax on production and sale of alcoholic beverages. The work has attempted to determine the motivation behind the names and to track down their development, while the applied research method involves the motivational analysis that results in a pool of particular types of surnames that includes surnames motivated by German proper names and German appellatives. The set of all foreign surnames of the population of Poznań, amounting to nearly 20% of all onomastic material attested in the available archival documents, includes far more German surnames or surnames of German origin than any other surnames. In time, the given names of German people were Polonized both in the phonetic and the morphological plane. A small part of them was incorporated into the Polish language in their original form. In the material under scrutiny the Polonized forms were in preponderance as compared to purely German names. Language adaptation was also responsible for the formation of surnames of women – hybrid feminine forms from German names with Polish feminine suffixes appended onto foreign names. On numerous occasions it was impossible to unequivocally establish the German etymology of some of the surnames, which forced a conclusion leading to a proposition of a multi-motivational character of Poznań anthroponyms that, beside the motivation by a Polish anthroponym or appellative, also referred to German anthroponyms and appellatives. The bulk of surnames of German origin have remained vital and have been testified in the resources of present-day Polish anthroponyms.